2021
DOI: 10.15549/jeecar.v8i2.713
|View full text |Cite
|
Sign up to set email alerts
|

Person-centered approach effectiveness in Human Resource Management in the agriculture of Azerbaijan

Abstract: The purpose of this study is to substantiate employee value (EV) and its impact on labor productivity in agriculture using the example of Azerbaijan. Using a survey of employees in agricultural enterprises, personnel values have been determined that determine the level of labor productivity in agriculture. A factor structure of EV has been determined, which has the following form: basic moral values, values of self-development and self-realization, democratic values, hedonistic values, dedication, tolerance, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…S. Guliyeva et al (2021), investigating a similar subject of the effectiveness of a personality-oriented approach in working with agricultural workers, identified that the development of employee value is directly proportional to labour productivity in the agro-industrial sector. According to the results of the analysis of the econometric model, the most stimulating factors influencing labour productivity in the agro-industrial complex were such values as the moral qualities of employees, a democratic approach in relations with subordinates, self-development, aid in self-fulfilment, tolerance, and dedication to the common cause.…”
Section: Discussionmentioning
confidence: 99%
“…S. Guliyeva et al (2021), investigating a similar subject of the effectiveness of a personality-oriented approach in working with agricultural workers, identified that the development of employee value is directly proportional to labour productivity in the agro-industrial sector. According to the results of the analysis of the econometric model, the most stimulating factors influencing labour productivity in the agro-industrial complex were such values as the moral qualities of employees, a democratic approach in relations with subordinates, self-development, aid in self-fulfilment, tolerance, and dedication to the common cause.…”
Section: Discussionmentioning
confidence: 99%
“…Starting from an initialized group, through random search process, crossover, and mutation operations, individuals are evolved, and the group gradually evolves to an optimized area in the search space to obtain the optimal solution [22]. (2) Information Exchange between Individuals.…”
Section: Overview Of Genetic Algorithm Usementioning
confidence: 99%
“…Rural migrant laborers are often treated unfairly in the community, and the new generation of rural migrant laborers are eager to integrate into the city, but lack channels to participate in urban public life, resulting in low identification of rural migrant laborers with their own citizenship (Xu & Shi, 2020). When the working hours of rural migrant laborers are too long, they do not have time to participate in social activities, which hinders the rural transfer labor force to accumulate social capital, which affects the integration of rural transfer labor into urban life and thus affects urban identity (Pan & Lin, 2015;Guliyeva et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%